2012
DOI: 10.1186/1479-5876-10-109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AEG-1 mRNA and protein in colorectal cancer patients and colon cancer cell lines

Abstract: BackgroundAstrocyte elevated gene 1 (AEG-1), an important oncogene, has been shown to be overexpressed in several types of cancers. In colorectal cancer (CRC), the protein level of AEG-1 is up-regulated in tumour tissue compared to normal mucosa, showing prognostic significance. Since little is known about the transcriptional level of AEG-1 expression and its biological pathway in CRC the aim of the present study was to examine the relationship of AEG-1 mRNA expression, the protein level and clinicopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 40 publications
2
63
0
Order By: Relevance
“…Moreover, we found that AEG-1 expression was not related to patient survival in CRC (Gnosa et al , 2012). Further survival analysis on the same cohort revealed no correlation of the AEG-1 expression with survival in either colon cancer patients or in rectal cancers patients (S Gnosa, unpublished data).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, we found that AEG-1 expression was not related to patient survival in CRC (Gnosa et al , 2012). Further survival analysis on the same cohort revealed no correlation of the AEG-1 expression with survival in either colon cancer patients or in rectal cancers patients (S Gnosa, unpublished data).…”
Section: Discussionmentioning
confidence: 84%
“…The AEG-1 is markedly overexpressed in many types of cancers compared with normal cells, including oesophageal squamous cell carcinoma (Yu et al , 2009), gastric cancer (Jian-bo et al , 2011), CRC (Gnosa et al , 2012), hepatocellular carcinoma (Yoo et al , 2009), non-small-cell lung cancer (Song et al , 2009), neuroblastoma (Lee et al , 2009), breast cancer (Brown and Ruoslahti, 2004; Li et al , 2008), prostate cancer (Thirkettle et al , 2009), and renal cancer (Chen et al , 2010). …”
mentioning
confidence: 99%
“…AEG-1 overexpression suppressed apoptosis by regulating phosphorylation of Akt substrates glycogen synthase kinase 3β, c-Myc, p53, and B-cell lymphoma-2 associated death promoter (Lee et al , 2008). AEG-1 was also induced after DNA damage and implicated in p53 independent apoptotic pathway by activating NF-κB (Gnosa et al , 2012). Additionally, opening of mitochondrial transition pores, an indicator of cell death, is enhanced in tissues of aged mice (Mather and Rottenberg, 2000).…”
Section: Astrocytes and Aeg-1 In Agingmentioning
confidence: 99%
“…Gnosa et al (2012) analyzed AEG-1/MTDH/LYRIC mRNA expression by qPCR in primary tumor and adjacent normal mucosa from 156 CRC patients, and AEG-1/MTDH/LYRIC protein expression by IHC in 74 distant normal colorectal mucosa, 107 adjacent normal colorectal mucosa, 158 primary CRC, 35 lymph node metastases, and 9 liver metastases. The mean level of AEG-1/MTDH/LYRIC mRNA was 371.56±348.37 in the primary tumor and 214.98±156.39 in the adjacent normal mucosa in 156 patients ( p =0.0005).…”
Section: Gastrointestinal Systemmentioning
confidence: 99%